Perceived Enablers of and Barriers to Serious Game as Oral Histology Learning Strategy for Undergraduate Dental Students - Lisa R. Amir; Salsabila N. Dewatmoko; Irene C. Leonardy; Rezon Yanuar; Dewi F. Suniarti; Erik Idrus; Kawin Sipiyaruk; Ria Puspitawati; Yuniardini Wimardhani (MDPI AG, 2024)
Previously, we reported the serious game HistoRM as an innovative learning approach for an oral histology course. This study aimed to examine the impact of HistoRM on summative assessment and the enablers and barriers factors affecting HistoRM as an interactive learning strategy in an oral histology course. A crossover randomized controlled trial was performed. Study participants were first-year dental students at the Universitas Indonesia. The average final grades of students who participated in HistoRM serious game were significantly higher than those of students who did not participate in this trial (p < 0.001). Positive responses of HistoRM were observed in the learning content, games and learning experience domains. The enabler factors most recognized by the students were the game method, which helped students to understand the learning materials; the immediate feedback provided following each gameplay; as well as the fun and interesting gameplay. The barrier factors most recognized by the students were some challenges of the gameplay, which resulted in a longer time needed to study. While the HistoRM serious game can stimulate student motivation and engagement in learning oral histology, overcoming the barriers is essential for the implementation of serious games as a complementary learning approach in the dental curriculum.